Digital Storytelling to Overcome Disruption: Exploring Local Heritage in an Online Environment - Batur, Monika; Barbarić, Ana (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie)

(untitled) (Canadian Association for Information Science - Association canadienne des sciences de l'information, 2026)
This study investigates how digital storytelling (DS) functions as a communicative strategy for the online presentation of local heritage. It aims to understand the extent to which DS mitigates digital disruption and supports inclusive, participatory, and identity-based narratives. The research applies a qualitative discourse analysis, complemented by a quantitative scope analysis, to a selected sample of 57 websites containing local heritage content. The analytical framework is organized into four levels of discourse analysis: textual, contextual, interactional/action-based, and ideological. The websites were evaluated according to narrative structure, emotional tone, multimodality, user interaction and curatorial authority. DS was identified in 60% of the websites in implicit, explicit or combined form. These DS strategies frequently include multimodal formats (text, audio, video, and image), personalized expression and emotionally resonant language. A recurring paradox was observed: while visual design is becoming more minimalistic, narrative richness is increasing. Most websites exhibited integrative and micro-historical approaches; however, a subset retained institutional or canon-based frameworks that limit narrative diversity. Methodologically, the study underscores the need to adapt discourse analysis to multimodal and non-linear environments. It also highlights the significance of curatorial power in shaping digital heritage narratives. The findings are relevant to libraries, cultural institutions and digital curators seeking to enhance user engagement and inclusivity through narrative strategies. This research contributes to digital heritage, information science and internet studies by considering DS as a form of socio-technical resilience that supports meaning-making, identity and cultural memory in digitally mediated environments.